2020
DOI: 10.3390/cancers12051268
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Tissue-Based Classifier for Early Prediction of Prostate Cancer Progression

Abstract: Although ~40% of screen-detected prostate cancers (PCa) are indolent, advanced-stage PCa is a lethal disease with 5-year survival rates around 29%. Identification of biomarkers for early detection of aggressive disease is a key challenge. Starting with 52 candidate biomarkers, selected from existing PCa genomics datasets and known PCa driver genes, we used targeted mass spectrometry to quantify proteins that significantly differed in primary tumors from PCa patients treated with radical prostatectomy (RP) acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Proteomic studies in tissue, cell lines, blood, urine, seminal plasma, and exosomes have identified many potential biomarkers for PCa diagnosis, metastasis, aggressiveness, and resistance to treatment. These studies have utilized both untargeted gel-based and gel-free approaches, including two-dimensional gel electrophoresis coupled to mass spectrometry (2-DE-MS) [ 23 , 24 ], liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS), [ 25 , 26 , 27 ] and capillary electrophoresis coupled to mass spectrometry (CE-MS) [ 28 , 29 ], with LC-MS/MS being the most commonly used approach, as well as targeted mass spectrometry-based approaches [ 30 ]. The reproducibility of these findings remains challenging due to the heterogeneity of cancer itself and the various techniques used, but the data generated through these attempts is a great contribution to personalized approaches after more targeted investigations [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic studies in tissue, cell lines, blood, urine, seminal plasma, and exosomes have identified many potential biomarkers for PCa diagnosis, metastasis, aggressiveness, and resistance to treatment. These studies have utilized both untargeted gel-based and gel-free approaches, including two-dimensional gel electrophoresis coupled to mass spectrometry (2-DE-MS) [ 23 , 24 ], liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS), [ 25 , 26 , 27 ] and capillary electrophoresis coupled to mass spectrometry (CE-MS) [ 28 , 29 ], with LC-MS/MS being the most commonly used approach, as well as targeted mass spectrometry-based approaches [ 30 ]. The reproducibility of these findings remains challenging due to the heterogeneity of cancer itself and the various techniques used, but the data generated through these attempts is a great contribution to personalized approaches after more targeted investigations [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment strategies for PCa have been improved, the annual incidence of PCa has increased by 14% since 1990 (Ishizaki et al., 2012). Patients of early‐stage PCa often have a good prognosis after comprehensive treatment, but due to recurrence, metastasis and castration‐resistance, the 5‐year survival rate of patients with advanced‐stage PCa is only 29% (Gao et al., 2020). Unfortunately, although numerous studies have been implemented, the pathogenesis of tumorigenesis and progression of PCa has not been well elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
“…A classifier was created using differentially expressed proteins in formalin-fixed parafilm-embedded tissue specimens. This classifier comprised a panel of five proteins (i.e., FOLH1, KLK3, TGFB1, SPARC, and CAMKK2) that are capable of stratifying PCa patients according to the risk of aggressiveness [ 108 ]. In a recent study, seven differentially expressed proteins (i.e., HSPA9 and HSPE1, NPM1, VCAN, SERBP1, MRPL3, and UQCRH) were successfully used as indicators of PCa progression and aggressiveness [ 109 , 110 ].…”
Section: Tissue Prostate Cancer Biomarkersmentioning
confidence: 99%